Week 5 Discussion Notes

Table of Contents

Homework Comments

Now that the homework problems are a bit more interesting, I have relatively important comments to make.

1.9

This was the problem where you had to prove that 2n>n22^n > n^2 for all n5n \geq 5 by induction. I saw a lot of proofs that looked like this:

2n+1=22n>2n2>n2+2n+1(since n5)=(n+1)2.\begin{aligned} 2^{n+1} &= 2 \cdot 2^n \\ &> 2n^2 \\ &> n^2 + 2n + 1 && \p{\text{since } n \geq 5} \\ &= \p{n + 1}^2. \end{aligned}

I mainly had issue with the third line: while it is true that n2>2n+1n^2 > 2n + 1 when n5n \geq 5, you still have to prove it on your homework. As a general rule of thumb, you should prove all claims you make that weren't proven in lecture, discussion, or the book (unless Professor Jacobs or I say it's okay to take something for granted). That being said, here is one way to prove it: since n53n \geq 5 \geq 3,

n2=nn3n=2n+n>2n+1.n^2 = n \cdot n \geq 3n = 2n + n > 2n + 1.

Miscellaneous

Let P,QP, Q be propositional statements. If P    QP \implies Q is true and QQ is true, does this mean PP is also true? Hopefully, you agree that this is a false statement, and we can check with a logic table:

PQP    Q111100011001\begin{array}{ccc} P & Q & P \implies Q \\\hline 1 & 1 & 1 \\ 1 & 0 & 0 \\ 0 & 1 & 1 \\ 0 & 0 & 1 \\ \end{array}

The third row is the important row for this example: QQ is true and P    QP \implies Q is true, but PP is false. With this in mind, consider the following example:

Example 1.

What's the problem with the following argument?

Note that

n22n10    (n1)220    (n1)22.\begin{aligned} n^2 - 2n - 1 \geq 0 &\implies \p{n - 1}^2 - 2 \geq 0 \\ &\implies \p{n - 1}^2 \geq 2. \end{aligned}

This is true if n3n \geq 3. Therefore, n22n10n^2 - 2n - 1 \geq 0 when n3n \geq 3.

Solution.

While the conclusion is true, the proof (which is the most important part) is incorrect: set P=n22n10"P = ``n^2 - 2n - 1 \geq 0" and Q=(n1)22"Q = ``\p{n - 1}^2 \geq 2", and we assume that n3n \geq 3. Then the incorrect proof is using the following logic:

P    QP \implies Q is true and QQ is true. Therefore PP is true.

As we discussed, this logic is not correct. Instead, you should do this in reverse: show that something true implies something else is true. In this case, the proof is correct if we just reverse the order of the steps: for n3n \geq 3,

(n1)22    n22n+12    n22n10,\begin{aligned} \p{n - 1}^2 \geq 2 &\implies n^2 - 2n + 1 \geq 2 \\ &\implies n^2 - 2n - 1 \geq 0, \end{aligned}

and now you can conclude that n22n10n^2 - 2n - 1 \geq 0 for n3n \geq 3.

Limits

Limit Laws

Theorem (limit laws)

Suppose limnan=a\displaystyle\lim_{n\to\infty} a_n = a and limnbn=b\displaystyle \lim_{n\to\infty} b_n = b. Then:

  1. limn(an+bn)=a+b\displaystyle\lim_{n\to\infty} \p{a_n + b_n} = a + b.
  2. If cRc \in \R, then limncan=ca\displaystyle\lim_{n\to\infty} ca_n = ca.
  3. limn(anbn)=ab\displaystyle\lim_{n\to\infty} \p{a_nb_n} = ab.
  4. If b0b \neq 0, then limnanbn=ab\displaystyle\lim_{n\to\infty} \frac{a_n}{b_n} = \frac{a}{b}.

This looks like a straightforward theorem, but it can be very easy to misuse it. The most common way I've seen it be used incorrectly is trying to apply it with limits that don't exist.

Example 2.

If limnan\displaystyle\lim_{n\to\infty} a_n and limnbn\displaystyle\lim_{n\to\infty} b_n don't exist, does this mean an+bna_n + b_n doesn't exist?

Solution.

The following is wrong:

limn(an+bn)=limnan+limnbn\displaystyle\lim_{n\to\infty} \p{a_n + b_n} = \displaystyle\lim_{n\to\infty} a_n + \displaystyle\lim_{n\to\infty} b_n, and these limits don't exist. Therefore, limn(an+bn)\displaystyle\lim_{n\to\infty} \p{a_n + b_n} doesn't exist either.

The problem is with the first "=" sign: the limits don't exist, so that "=" is invalid. As a counterexample, consider an=(1)na_n = \p{-1}^n and bn=(1)nb_n = -\p{-1}^n. Then both limits don't exist, but

limn(an+bn)=limn((1)n(1)n)=limn0=0,\lim_{n\to\infty} \p{a_n + b_n} = \lim_{n\to\infty} \p{\p{-1}^n - \p{-1}^n} = \lim_{n\to\infty} 0 = 0,

so it's possible that the sum of two divergent sequences is convergent.

Exercise 1.

Come up with an example where {an}n\set{a_n}_n and {bn}n\set{b_n}_n are divergent, but {anbn}n\set{a_nb_n}_n is divergent.

Limit laws are very useful because if we can use them, then we don't need to do any ε\epsilon arguments.

Example 3.
(Related to 9.1, 9.3)

Suppose limnan=a\displaystyle\lim_{n\to\infty} a_n = a and limnbn=b\displaystyle\lim_{n\to\infty} b_n = b. Calculate limn2an2+1bn2+2\displaystyle \lim_{n\to\infty} \frac{2a_n^2 + 1}{b_n^2 + 2} and justify all your steps.

Solution.

This example is basically here to illustrate the amount of detail I expect on 9.1 and 9.3 (if you want full credit).

limnan=a\displaystyle\lim_{n\to\infty} a_n = a, so limn(2an2+1)=2a2+1\displaystyle\lim_{n\to\infty} \p{2a_n^2 + 1} = 2a^2 + 1 by (i), (ii), and (iii), and similarly, limn(bn2+1)=b2+1\displaystyle\lim_{n\to\infty} \p{b_n^2 + 1} = b^2 + 1 by (i) and (iii). Since b2+1>0b^2 + 1 > 0, we can use (iv) to get

limn2an2+1bn2+2=limn(2an2+1)limn(bn2+2)=2a2+1b2+2.\lim_{n\to\infty} \frac{2a_n^2 + 1}{b_n^2 + 2} = \frac{\lim_{n\to\infty} \p{2a_n^2 + 1}}{\lim_{n\to\infty} \p{b_n^2 + 2}} = \frac{2a^2 + 1}{b^2 + 2}.

Basically, every "=" needs to be justified (with a few words).

Another (very) useful theorem for calculating limits is the squeeze theorem:

Theorem (squeeze theorem)

Let {an}n\set{a_n}_n, {bn}n\set{b_n}_n, and {sn}n\set{s_n}_n be sequences such that ansnbna_n \leq s_n \leq b_n. If limnan=limnbn=L\displaystyle\lim_{n\to\infty} a_n = \lim_{n\to\infty} b_n = L, then limnsn=L\displaystyle \lim_{n\to\infty} s_n = L also.

Proof.

Let ε>0\epsilon > 0. Notice that

snLbnLbnLandanLanLsnL.s_n - L \leq b_n - L \leq \abs{b_n - L} \quad\text{and}\quad -\abs{a_n - L} \leq a_n - L \leq s_n - L.

Since limnan=L\displaystyle\lim_{n\to\infty} a_n = L, there exists N1RN_1 \in \R such that

n>N1    anL<ε    ε<anLsnL.\begin{aligned} n > N_1 &\implies \abs{a_n - L} < \epsilon \\ &\implies -\epsilon < -\abs{a_n - L} \leq s_n - L. \end{aligned}

Similarly, because limnbn=L\displaystyle\lim_{n\to\infty} b_n = L, there exists N2RN_2 \in \R so that

n>N2    bnL<ε    snLbnL<ε.\begin{aligned} n > N_2 &\implies \abs{b_n - L} < \epsilon \\ &\implies s_n - L \leq \abs{b_n - L} < \epsilon. \end{aligned}

These inequalities work for different conditions on nn, but we want to use them at the same time. If we let N=max{N1,N2}N = \max\,\set{N_1, N_2}, then whenever n>Nn > N, nn satisfies n>N1n > N_1 and n>N2n > N_2 at the same time. Thus,

ε<snL<ε    snL<ε.-\epsilon < s_n - L < \epsilon \implies \abs{s_n - L} < \epsilon.

\square

We generally use the following corollary of the squeeze theorem the most:

Corollary

Let {sn}n\set{s_n}_n and {tn}n\set{t_n}_n be sequences such that sntn\abs{s_n} \leq t_n and limntn=0\displaystyle\lim_{n\to\infty} t_n = 0. Then limnsn=0\displaystyle\lim_{n\to\infty} s_n = 0.

Proof.

Observe that tnsntn-t_n \leq s_n \leq t_n. Thus, if we set an=tna_n = -t_n and bn=tnb_n = t_n as in the theorem, then ansnbna_n \leq s_n \leq b_n and

limnan=limnbn=0    limnsn=0.\lim_{n\to\infty} a_n = \lim_{n\to\infty} b_n = 0 \implies \lim_{n\to\infty} s_n = 0.

\square

This corollary helps speeds up proofs quite a bit:

Example 4.

Prove that limnn+2n2+1=0\displaystyle \lim_{n\to\infty} \abs{\frac{n + 2}{n^2 + 1}} = 0.

Solution.

In light of the squeeze theorem, we just need to find something bigger than n+2n2+1\abs{\frac{n + 2}{n^2 + 1}} which goes to 00:

n+2n2+1n+nn22nn0.\abs{\frac{n + 2}{n^2 + 1}} \leq \frac{n + n}{n^2} \leq \frac{2}{n} \xrightarrow{n\to\infty} 0.

(The arrow can be read as "... which goes to 00 as nn \to \infty".)

Proving Divergence

As a quick example (relevant for your homework), here are two problems where you need to show that a limit doesn't exist:

Example 5.

Let a2n=1a_{2n} = 1 and a2n+1=3a_{2n+1} = 3. Show that limnan\displaystyle\lim_{n\to\infty} a_n does not exist.

Solution.

Suppose otherwise and that limnan=L\displaystyle\lim_{n\to\infty} a_n = L. Then given ε>0\epsilon > 0, there exists NRN \in \R such that whenever anL<ε\abs{a_n - L} < \epsilon whenever n>Nn > N.

Suppose k>N2k > \frac{N}{2}. Then

2k>N    a2kL<ε.2k > N \implies \abs{a_{2k} - L} < \epsilon.

Similarly,

2k+1>N    a2k+1L<ε.2k + 1 > N \implies \abs{a_{2k+1} - L} < \epsilon.

Based on these inequalities, if nn is big enough, then LL is within ε\epsilon of 11 and 33. In the picture, this means that LL has to be in both blue parentheses, and this should be impossible if ε\epsilon is small enough. Based on the picture, we should get a contradiction if we let ε=1\epsilon = 1:

2=13=a2ka2k+1a2kL+a2k+1L<1+1=2.2 = \abs{1 - 3} = \abs{a_{2k} - a_{2k+1}} \leq \abs{a_{2k} - L} + \abs{a_{2k+1} - L} < 1 + 1 = 2.

This is impossible, so no LL could have existed to begin with, which completes the proof.

Example 6.

Let an=2na_n = 2^n. Prove that limn2n\displaystyle\lim_{n\to\infty} 2^n does not exist.

Solution.

Like before, we're going to assume (for the sake of contradiction) that limnan=L\displaystyle\lim_{n\to\infty} a_n = L.

We're going to apply the same strategy: we're going to pick ε\epsilon small enough so that LL would have to be in two different places at the same time, which should give us a contradiction. Based on the picture, the distance between 2n2^n and 2n+12^{n+1} is 2n22^n \geq 2, so ε=1\epsilon = 1 should work again.

By definition of the limit, there exists NRN \in \R such that if n>Nn > N, then anL<1\abs{a_n - L} < 1. Notice this means that an+1L<1\abs{a_{n+1} - L} < 1 as well, so

2n=anan+1anL+an+1L<1+1=2.2^n = \abs{a_n - a_{n+1}} \leq \abs{a_n - L} + \abs{a_{n+1} - L} < 1 + 1 = 2.

Thus, we get a contradiction, so the limit must not have existed to begin with.